PENGARUH KARAKTERISTIK INDIVIDU, IKLIM ORGANISASI DAN PROMOSI JABATAN TERHADAP KINERJA KARYAWAN - Ratnawili Ratnawili; Dinda Pramudita (UM. Bengkulu, 2023)
The purpose of this study was to determine the effect of individual characteristics, organizational climate, and promotion on the performance of employees at PT. North Bengkulu Agriculture. Several factors will be discussed in this study, including the influence of individual characteristics, organizational climate and employee performance. The objects in this study are employees at PT Agricinal Bengkulu Utara. The objects in this study were 171 employees at PT Agricinal Bengkulu. Data collection techniques in research are observation and questionnaires. There are several data analysis techniques used in this study, including descriptive analysis, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. Based on the research results, the following conclusions can be drawn: Individual characteristics (X1) have a positive effect on employee performance (Y) PT. North Bengkulu Agricinal means that if individual characteristics increase, employee performance also increases. Organizational climate (X2) has a positive effect on employee performance (Y) PT. North Bengkulu Agricinal means that if the organizational climate is good then the employee performance is also good. Promotion (X3) has a positive effect on employee performance (Y) PT. North Bengkulu Agricinal means that if the promotion increases, the employee's performance also increases. Individual characteristics, organizational climate and promotion together have a positive effect on the performance of employees of PT. North Bengkulu Agriculture. Keywords: Individual Characteristics, Organizational Climate, Promotion, Employee Performance